PENGARUH MOTIVASI DAN DISPLIN KERJATERHADAP KINERJA PEGAWAI NON PNSPADA KANTOR KECAMATAN SETU KOTA TANGERANG SELATAN - Fikry, Muhammad Alif; Yunanti, Siska (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of motivation and work discipline on the performance of non-PNS employees at the Setu sub-district office, South Tangerang city, both partially and simultaneously. The method used is associative quantitative. The sampling technique used saturated sampling and the sample obtained in this study was 60 respondents. Data analysis uses validity tests, reality tests, classical assumption tests, quantitative analysis, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The research results obtained were multiple linear regression Y = 18.003 + 0.334X1 + 0.389X2. The correlation coefficient value is 0.580. The coefficient of determination of the motivation variable (X1) and work discipline (X2) contributes 33.7%. The calculated t value > t table or (11.650 > 2.002) so that H0 is rejected and H1 is accepted, meaning that there is a partial positive and significant influence between motivation (X1) on employee performance (Y). The calculated t value > t table or (4.914 > 2.002) so that H0 is rejected and H2 is accepted, meaning that there is a partially positive and significant influence between work discipline (X2) on employee performance (Y). The calculated F value > F table or (14.458 > 3.160) so that H0 is rejected and H3 is accepted, meaning that there is a positive and significant influence simultaneously between motivation (X1) and work discipline (X2) on employee performance (Y).